2010
DOI: 10.1029/2009ja014480
|View full text |Cite
|
Sign up to set email alerts
|

Can intense substorms occur under northward IMF conditions?

Abstract: [1] This paper reports on several substorms observed under northward interplanetary magnetic field (IMF) conditions, the intensity of which was at least as significant as that of typical substorms under moderately southward IMF conditions. Such northward IMF periods were identified during the recovery phase of three strong storms. In the case of each storm, two or more substorms occurred successively, being separated by $1.8-5 h, while the IMF condition continued persistently northward. The substorms are clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 38 publications
(51 reference statements)
1
66
1
Order By: Relevance
“…It appears that the X line during quiet time is attributed to the northward IMF condition. Substorms can occur for southward as well as northward IMF [Akasofu et al, 1973;Lui et al, 1976;Lee et al, 2010]. However, substorms are much weaker for northward than southward IMF conditions [Petrukovich et al, 2000;Kullen and Karlsson, 2004;Pulkkinen et al, 2007;Peng et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the X line during quiet time is attributed to the northward IMF condition. Substorms can occur for southward as well as northward IMF [Akasofu et al, 1973;Lui et al, 1976;Lee et al, 2010]. However, substorms are much weaker for northward than southward IMF conditions [Petrukovich et al, 2000;Kullen and Karlsson, 2004;Pulkkinen et al, 2007;Peng et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…However, substorms are at times also observed during quiet periods with positive B IMF z . Lee et al (2010) report on several substorms observed under positive B IMF z conditions, the intensity of which was at least as significant as that of typical substorms under moderate negative B IMF z . These substorms occurred during the recovery phase of intense magnetic storms.…”
Section: Behaviour Of the Discrete Auroral Formsmentioning
confidence: 99%
“…Delays normally have never been longer than one or at most two hours when the Dst index starts to decrease. Lee et al (2010) in their recent paper entitled "Can intense substorms occur under northward IMF conditions" mention that the occurrence of such (intense) substorms implies that a certain (large) amount of energy remains in the tail even under northward IMF conditions. Crowley et al (2010) also showed that large amounts of energy can be deposited into the high latitude regions during B z northward or strong B y conditions, driving large perturbations in the neutral density at times when they would not previously have been expected.…”
Section: Introductionmentioning
confidence: 99%
“…Du et al (2008) have investigated the storm on 21-22 January 2005 and called it an "anomalous" geomagnetic storm as the storm main phase occurs during northward interplanetary magnetic fields (IMFs). As described by Lee et al (2010), a southward IMF condition is generally considered to be the most fundamental precondition for a storm or substorm to occur. The Dst index typically starts to decrease about an hour after the IMF turns southward.…”
Section: Introductionmentioning
confidence: 99%